2
$\begingroup$

I am trying to show that for any real $a,b,c,d$ we have

$$ \left| (|a|-|b|)-(|c|-|d|) \right| \le \left| (a-b)-(c-d) \right| $$

At a glance, it seems like this cannot be true, but I haven't been able to come up with a counter example. Furthermore, it is not to hard to establish that

$$ \left| |a-b|-|c-d| \right| \le \left| (a-b)-(c-d) \right|. $$

For example by the (reverse) triangle inequality we have either $$ \left| |a-b|-|c-d| \right| = |a-b|-|c-d| \le |(a-b)-(c-d)| $$ or $$ \left| |a-b|-|c-d| \right| = |c-d|-|a-b| \le |(c-d)-(a-b)| = |(a-b)-(c-d)| .$$

And it seems much more believable that possibly $$ \left| (|a|-|b|)-(|c|-|d|) \right| \le \left| |a-b|-|c-d| \right|$$ could hold, establishing the desired result.

$\endgroup$

1 Answer 1

2
$\begingroup$

A counterexample is $a=1,b=c=0,d=-1$.

$\endgroup$
2
  • $\begingroup$ Dang. I knew it would be obvious and was reluctant to post for that reason. Thank you nonetheless. I wonder then what additional restrictions could make the above true. All nonzero? All $a,b,c,d$ distinct? Not really at all? In any case I think under too many more restrictions the inequality above loses all usefulness anyway. $\endgroup$ Jan 26, 2022 at 17:13
  • $\begingroup$ Glad to have helped. I cannot see any restrictions to make it work other than ones which make it too trivial. $\endgroup$
    – user502266
    Jan 26, 2022 at 17:19

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .